Development of T-ARMS-PCR to Detect MYBPC3 Gene Variation in Hypertrophic Cardiomyopathy (HCM) Patients - Sadia, Haleema; Ahmed Khan, Waqas; Hussain, Misbah; Murtza, Iqra (Current Trends in OMICS, 2023)
Hypertrophic cardiomyopathy (HCM) is a common and complex, genetically inherited, cardiovascular disorder. It is typically inherited in an autosomal dominant manner with variable penetrance and mutable expression. Mutations in MYBPC3 gene is one of the genetic causes of HCM. Only 0.2% of general population suffers from HCM. The MYBPC3 gene provides instructions for making cardiac myosin binding protein C, which is imperative for the maintenance and regulation of normal cardiac functions. This study aims to explore the reported SNP rs1052373 from exon 30 of MYBPC3 gene in the population of Punjab, Pakistan. The reported SNP rs1052373 was analysed using Tetra Amplification Refractory Mutation System Polymerase Chain Reaction (T-ARMS-PCR) to find the allelic frequency in the selected population. T-ARMS-PCR is a cost effective, flexible, rapid, and accurate tool for genotyping. The specific sequences of MYBPC3 gene from exons 30 and 31 and introns 29, 30, and 31 were retrieved from NCBI (https://www.ncbi.nlm.nih.gov/). A tetra primer designing tool known as Primer 1 (http://primer1.soton.ac.uk/primer1.html) was used to design the primers for the targeted region of MYBPC3 gene. In this study, the genotyping of previously reported SNP rs1052373 showed variation in the disease group, giving CC, CT, and TT genotypes with the frequency of 0.04. The genotyping analysis of rs1052373 showed that the allelic frequency of homozygous condition T/T was 0.02 and the allelic frequency of heterozygous condition C/T was 0.02 in disease group as compared to the control group. In the latter, the homozygous T/T and heterozygous C/T genotypes were not observed in any individuals. All the individuals in control group carried homozygous C/C genotype. While, the frequency of homozygous C/C genotype was 0.96 in disease group. The findings of this study would help to find novel molecular markers for HCM diagnosis.